Pseudomonas aeruginosa mutants altered in their sensitivity to the effect of iron on toxin A or elastase yields. - Sokol, P A (1982)
Iron affects yields of toxin A, alkaline protease, elastase, pyochelin, and pyoverdin in Pseudomonas aeruginosa. Mutants of P. aeruginosa PAO1 resistant to the effect of iron on toxin (toxC) or elastase (elaC) yields were isolated. Two types of mutants were isolated: iron transport and iron regulatory mutants. The toxC regulatory mutants produced toxin A in medium containing iron; however, yields of elastase and alkaline protease remained sensitive to regulation by iron. The elaC regulatory mutants were resistant to the effect of iron on elastase yields, but toxin A and alkaline protease yields were decreased by iron, analogous to the parent strain. These data suggest that toxin A, elastase, and alkaline protease yields can be independently regulated by iron.